Konsep Perlindungan Tawanan Perang Menurut Hukum Humaniter Internasional dan Hukum Islam - Hanung Hisbullah Hamda (Fakultas Hukum Universitas Islam Indonesia, 2005)
Generally, there isno fundamental contradiction between concept of International Humanitaraian Law and Islamic Lawin protecting prisoners of war. But there arestili differences in operationalfield. Both intemational Humanitaraian Law and Islamic Law protect the rights of prisoners ofwar in medical support, their human values and their right to getprotection guarantee. Both concepts also have a mutual dependence, because some West scholars admitted that treatment concept of prisoners of war in Intemational Humanitarian Law adopted from Islamic concept